2011
DOI: 10.1038/gene.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

IL28B genetic variations are associated with high sustained virological response (SVR) of interferon-α plus ribavirin therapy in Taiwanese chronic HCV infection

Abstract: Chronic hepatitis C virus (HCV) infection patients exhibit different sustained virological responses (SVRs) following the treatment with pegylated interferon-α (IFN-α) and ribavirin. Genome-wide association studies consistently linked SVR of IFN-α-based therapy to the IL28B single-nucleotide polymorphisms (SNPs) on chromosome 19q.13 in various populations. This study was undertaken to investigate the association of IL28B SNPs with SVR in a cohort of Taiwanese chronic HCV patients. Ten SNPs of IL28B were genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 59 publications
3
37
2
1
Order By: Relevance
“…As shown in Table I, 16 studies (10,13,21-34) were eligible for examining the association between the IL28B polymorphism rs8099917 and treatment response of hepatitis C, including 3,540 cases with SVR and 2,208 cases with non-SVR. As shown in Table II, 17 studies (4,10,17,21,(27)(28)(29)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) were eligible for examining the association between the IL28B polymorphism rs12979860 and treatment response of hepatitis C, including 2,951 cases with SVR and 2,506 cases with non-SVR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table I, 16 studies (10,13,21-34) were eligible for examining the association between the IL28B polymorphism rs8099917 and treatment response of hepatitis C, including 3,540 cases with SVR and 2,208 cases with non-SVR. As shown in Table II, 17 studies (4,10,17,21,(27)(28)(29)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) were eligible for examining the association between the IL28B polymorphism rs12979860 and treatment response of hepatitis C, including 2,951 cases with SVR and 2,506 cases with non-SVR.…”
Section: Resultsmentioning
confidence: 99%
“…For rs8099917, patients with the TT genotype (2,819/4,106) had a higher rate of SVR than G allele carriers (721/1,642) from 16 studies (TT vs. TG/GG, OR=2.29, 95% CI 1.74-3.01, P<0.001 for heterogeneity). Of these 16 studies, seven (21,25,26,28,(30)(31)(32) examined the association between IL28B polymorphism rs8099917 and the SVR rate in an Asian population, and the other nine in a European population. The SVR rate in Asian patients (2,160/3,426) was higher than that in European patients (1, Table I.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the interleukin-28B polymorphism was associated with a high SVR rate in the two studies which reported relevant data. 26,72 End-of-treatment responses were recorded in 49 studies. The pooled estimate of the proportion of patients who achieved an end-of-treatment response was higher: (i) for those who were HIV− than for those who were HIV+, at 74% versus 52%, respectively; (ii) for those who received ribavirin than for those who did not, at 69% versus 51%, respectively; and (iii) for those who received pegylated rather than standard interferon, at 73% versus 62%, respectively.…”
Section: Study Outcomesmentioning
confidence: 99%
“…In contrast, especially association of IL28B variants with HCV therapy failure have been repeatedly reported from several independent large cohorts band are therefore being considered as ''state of the art'' in HCV pharmacogenetics [16]. Moreover, IL28B genetics have been verified to apply to different ethnicities such as Caucasians [17] and Asians [18]. However, while IL28B rs12979860 was the most significant variant in Caucasians, African Americans and Hispanics [19], in Japanese it seems more likely to be the rs8099917 SNP, which was nevertheless also significant in the other cohorts [20].…”
Section: Literature Search Strategymentioning
confidence: 91%